Proceedings of the 2015 International Conference on Education, Management, Information and Medicine 2015
DOI: 10.2991/emim-15.2015.113
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Changes of Aster Tataricus Main Chemical Compositions Before and After Honey-Roasting

Abstract: Abstract. Objective: To study the changes of the traditional Chinese medicine Aster tataricus Linn's main chemical compositions before and after honey-roasted, and analyze the main chemical compositions of its two different processed products which includes crude or Honey-roasted. Methods: Using ultraviolet spectrophotometry to measure the content of total triterpenoids and total flavonoids in crude and honey-roasted Aster tataricus L.; The Thin Layer Chromatography (TLC) was employed to compare the changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other compounds with negligible changes in content included scopoletin, quercetin, luteolin, and isorhamnetin. 46 For the total content, a report by Liu et al 47 showed that the honey-roasted Zi Wan had a higher content of total flavonoids and total triterpenoids than the sliced Zi Wan.…”
Section: Pharmacological Activities There Have Been Several Papers Ab...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other compounds with negligible changes in content included scopoletin, quercetin, luteolin, and isorhamnetin. 46 For the total content, a report by Liu et al 47 showed that the honey-roasted Zi Wan had a higher content of total flavonoids and total triterpenoids than the sliced Zi Wan.…”
Section: Pharmacological Activities There Have Been Several Papers Ab...mentioning
confidence: 99%
“…Terpenoids, flavonoids, peptides, coumarins, anthraquinones, and organic acids 44 -Increase: Content of total flavonoid and triterpenoid (protocatechuic acid, isoquercitrin, and kaempferol-7-O-β-D-glucopyranoside) 47 -Increase: Anti-inflammatory effect 48 -Decrease: Content of phenolic aicds (chlorogenic acid, caffeic acid, 7-hydroxycoumarin, ferulic acid, kaempferol, shionon, and epifriedelinol) 46 -Decrease: bioavailability 49 -There was a difference in chemical composition of 22 nonvolatile compounds and 12 volatile compounds 45 NY: Not yet.…”
Section: Ma Huangmentioning
confidence: 99%